2019
DOI: 10.1007/s11883-019-0762-1
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Mechanisms of Action for Omega-3 Fatty Acids in Atherothrombotic Cardiovascular Disease

Abstract: Purpose of ReviewTreatment of hypercholesterolemia with statins results in significant reductions in cardiovascular risk; however, individuals with well-controlled low-density lipoprotein cholesterol (LDL-C) levels, but persistent high triglycerides (TG), remain at increased risk. Genetic and epidemiologic studies have shown that elevated fasting TG levels are associated with incident cardiovascular events. At effective doses, omega-3 fatty acids, such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(41 citation statements)
references
References 82 publications
0
41
0
Order By: Relevance
“…However, controversies exist on this topic [10]. Recently, EPA was shown to improve endothelial function [52]. This is crucial since endothelial cells are considered the gatekeeper of vascular health.…”
Section: Discussionmentioning
confidence: 99%
“…However, controversies exist on this topic [10]. Recently, EPA was shown to improve endothelial function [52]. This is crucial since endothelial cells are considered the gatekeeper of vascular health.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings concerning nutraceutical-mediated triglyceride-lowering have renewed the focus on lipids other than LDL-C. Evidence from RCTs, observational studies, and meta-analyses strongly suggest that consumption of oily fish and long-chain omega-3 polyunsaturated fatty acids (PUFAs) improves risk factors and biomarkers associated with cardiovascular disease [19,29,30], in a manner consistent with the understanding of the biological actions of PUFAs, in particular the triglyceridelowering effects of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) [31]. Because these active components can be chemically identified and standardized and appear to be closely associated with improvements in risk factors, PUFAs are an attractive target for nutraceutical development, and unusually for the field of nutraceutical research, three large, rigorous clinical trials have been published.…”
Section: Nutraceuticals To Manage Residual Risk Associated With Lipidmentioning
confidence: 89%
“…REDUCE-IT had a mineral oil placebo, whereas STRENGTH had a corn oil placebo. An in vitro study has shown that EPA has direct antioxidant benefits in various apoBcontaining particles that are more pronounced than those of DHA and other TGlowering agents [185]. Although all these differences may explain partially the inconsistent results in the two studies, it appears most plausible that EPA may have different biological effects on CV events compared with those of DHA.…”
Section: Success Factors In the Reduce-it Studymentioning
confidence: 99%
“…The daily dosage of n-3 supplements is usually 2 capsules containing the combination of 180 mg EPA and 120 mg DHA (=0.6 g/ day of n-3), and no more than 2 g/day as dietary n-3 supplements in the FDA recommendation of 2014 [183]. The rationale of 4 g EPA in REDUCE-IT was that the blood concentration at this dose (183 μg/ml) was similar to that in Japanese subjects in JELIS study who received 1.8 g of EPA (170 μg/ml) [156,185]. This occurred because Japanese people have much higher background intake of fish and thus have higher EPA and DHA blood concentrations than seen in Western populations.…”
Section: Success Factors In the Reduce-it Studymentioning
confidence: 99%